Key Odorants from Pig Production Based on Improved Measurements of Odor Threshold Values Combining Olfactometry and Proton-Transfer-Reaction Mass Spectrometry (PTR-MS) - Michael Jørgen Hansen; Pernille Lund Kasper; Anders Peter S. Adamsen; Anders Feilberg (Sensors, 2018)
Analytical measurements of odorants in combination with odor threshold values is an alternative to sensory measurements that can be used to evaluate abatement technologies for pig production facilities. The purpose of the present study was to estimate odor threshold values for key odorants found in pig house air. A new method was applied where an olfactometer was used to dilute the sample air and the concentrations of odorants presented to the panelists at the dilutions steps were measured by proton-transfer-reaction mass spectrometry (PTR-MS). The results demonstrate that the odor threshold values of acetic acid, butanoic acid, and 4-methylphenol are considerably lower than reported previously, whereas the values of hydrogen sulfide, methanethiol and dimethylsulfide were comparable. Consequently, acetic acid, butanoic acid, and 4-methyl-phenol will have a larger influence on odor from pig production facilities than previously assumed. The results highlight the necessity for directly measuring exposure concentrations when determining odor threshold values.